Bureaucratic Behavior and Utilization of Online Single Submission (OSS) Technology - Nur Mulyani Sari; Bachtari Alam Hidayat; Rika Destiny Sinaga (Nakhoda: Jurnal Ilmu Pemerintahan)
Bureaucratic behavior in Indonesia is often criticized for being slow, convoluted, and lacking transparency, ultimately reducing investor interest at the regional level. Meanwhile, business actors frequently face challenges in understanding and utilizing the Online Single Submission (OSS) system, particularly due to limited socialization, low digital literacy, and mismatches between the system and practical needs. Ogan Ilir Regency, as a developing region in South Sumatra Province, holds significant investment potential. However, investment acceleration in the region remains suboptimal. This study aims to analyze the influence of bureaucratic behavior and business actor behavior in the implementation of the OSS system on investment acceleration in Ogan Ilir Regency. This study employed a descriptive quantitative approach. The independent variables were bureaucratic behavior (X1) and business actor behavior (X2), while the dependent variable was investment acceleration (Y). The sample was determined using total sampling, involving 50 respondents consisting of licensing bureaucrats, business actors who use OSS, local government officials, and IT staff. Data were collected using a questionnaire comprising 26 items, assessed with a 4-point Likert scale. Validity and reliability tests were conducted, and data were analyzed using multiple linear regression with the help of SPSS 25. The results indicate that both bureaucratic behavior and business actor behavior have a significant influence on investment acceleration in Ogan Ilir Regency. The findings affirm that the success of OSS in accelerating investment depends not only on technological infrastructure but also on human behavior. Small and medium enterprises (SMEs) still require special assistance and mentoring to boost their confidence in utilizing digital platforms and complying with regulations. With increasing adaptability of business actors to OSS, investment processes can be expedited, fostering local economic growth and creating a more competitive and inclusive business environment in Ogan Ilir.